Evaluation of the Implementation of Spelling and Administrative Writing Standards in Official Statements of Amplas Village, Percut Sei Tuan District - Tri Budiarti Damanik; Sry Novita Tondang (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study aims to: 1) assess the accuracy of the application of the Indonesian Spelling Standards (EYD) Edition V on official letters issued by the village government; 2) evaluate the completeness of the administrative elements in official letters issued by the village government. The study was conducted at the Amplas Village Office, Percut Sei Tuan District, Deli Serdang Regency, North Sumatra Province, Indonesia, from September to October 2025. The study population was the entire archive of village official letters. A sample of 20 official letters was determined purposively based on the type and completeness of the documents. The research instruments were a linguistic assessment sheet covering the use of capital letters, punctuation, and standard word choice, as well as an administrative evaluation sheet covering the completeness of official letter components. Data analysis was conducted using a qualitative descriptive method with an evaluative approach, accompanied by the assignment of appropriateness scores and percentage calculations for each assessment aspect. The results showed that: 1) the administrative aspects of official letters were in the very good category with a percentage score ranging from 83–92 percent; 2) the completeness and accuracy of the administrative structure had been consistently met. The linguistic aspect shows persistent inaccuracies in the use of capital letters, punctuation, and standard words, with scores ranging from 8 to 17. Overall, the quality of the Amplas Village certificate is in the good category, with the main weakness being the consistency of the application of linguistic rules.